2018
DOI: 10.1016/j.anorl.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of the thyroid associated with papillary thyroid carcinoma and Hashimoto's thyroiditis

Abstract: In conclusion, the most probable origin of SCC in this case was malignant transformation from Hashimoto's thyroiditis following a phase of metaplasia. This immunohistological profile is associated with a better prognosis. Optimal treatment consists of extensive surgical resection of tumour tissuefollowed by radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…Giuseppa G et al found that in a study of 305 cases of PTC divided into two groups, up to 40.2% of the patients coexisted both diffuse HT and PTC in one group, and the results of this study indicated that the coexistence of HT and PTC was very high (4). Several other studies have also shown that HT is closely related to PTC (2,5,21,22). Studies also suggested that HT might be an independent risk factor for thyroid cancer (23).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Giuseppa G et al found that in a study of 305 cases of PTC divided into two groups, up to 40.2% of the patients coexisted both diffuse HT and PTC in one group, and the results of this study indicated that the coexistence of HT and PTC was very high (4). Several other studies have also shown that HT is closely related to PTC (2,5,21,22). Studies also suggested that HT might be an independent risk factor for thyroid cancer (23).…”
Section: Discussionsupporting
confidence: 56%
“…HT is the most common thyroid immune diseases. There is overwhelming evidence to show that HT is closely related to thyroid cancer, especially PCT (2)(3)(4)(5)(6)(7)(21)(22)(23). Giuseppa G et al found that in a study of 305 cases of PTC divided into two groups, up to 40.2% of the patients coexisted both diffuse HT and PTC in one group, and the results of this study indicated that the coexistence of HT and PTC was very high (4).…”
Section: Discussionmentioning
confidence: 54%
“…The origin of ThySCC is not well understood. Some have suggested an 'embryonic-rest' theory of ThySCC development, whereby these cancerous cells develop from thyroglossal duct remnants, while another, more widely accepted theory, is that ThySCC results from squamous metaplastic transformation of other thyroid tumors [2][3][4][5]. The metaplastic theory is supported by the observation that approximately 40% of papillary thyroid cancers (PTC), along with many ATCs, contain regions of squamous metaplasia [6].…”
Section: Introductionmentioning
confidence: 99%
“…In ltration of cervical lymph nodes may or may not be present. [5][6] Clinically anaplastic thyroid carcinoma is the main differential diagnosis. In our case histologically very evident squamous cell differentiation was seen, we could not detect any other component after cut up the whole specimen.…”
Section: Discussionmentioning
confidence: 99%